2022
DOI: 10.4014/jmb.2205.05006
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antibacterial, Cytotoxic and Catalytic Activities of Silver Nanoparticles Synthesized from Acidophilic Actinobacterial SL19 with Evidence for Protein as Coating Biomolecule

Abstract: Silver nanoparticles (AgNPs) have potential applications in medicine, photocatalysis, agriculture, and cosmetic fields due to their unique physicochemical properties and strong antimicrobial activity. Here, AgNPs were synthesized using actinobacterial SL19 strain, isolated from acidic forest soil in Poland, and confirmed by UV-vis and FTIR spectroscopy, TEM, and zeta potential analysis. The AgNPs were polydispersed, stable, spherical, and small, with an average size of 23 nm. The FTIR study revealed the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 86 publications
1
13
0
Order By: Relevance
“…Frontiers in Microbiology 10 frontiersin.org on the surface of the AgNPs (Elumalai et al, 2017;Wypij et al, 2022). The presence of biomolecules on the surface of synthesized AgNPs was confirmed by FT-IR measurements which revealed characteristic peaks.…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Frontiers in Microbiology 10 frontiersin.org on the surface of the AgNPs (Elumalai et al, 2017;Wypij et al, 2022). The presence of biomolecules on the surface of synthesized AgNPs was confirmed by FT-IR measurements which revealed characteristic peaks.…”
Section: Discussionmentioning
confidence: 80%
“…However, several unassigned peaks were also recorded in the XRD analysis. It is suggested that these additional peaks arise due to the crystallization of the bioorganic phase on the surface of the AgNPs ( Elumalai et al, 2017 ; Wypij et al, 2022 ). The presence of biomolecules on the surface of synthesized AgNPs was confirmed by FT-IR measurements which revealed characteristic peaks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations